Factors involved in the infant feeding intention during postpartal confinement and the method of infant feeding at six to eight weeks postpartum - Botin, Cheryle Ann F.
This is a study to determine the factors involved in the infant feeding intention during postpartal confinement and the method of infant feeding at 6 to 8 weeks postpartum.The objectives of the study are a) to determine if maternal attitudes towards infant feeding, social influences and perceived behavioral control over breast-feeding are associated with sustaining the infant feeding intention; b) to find out if there are changes in the mean scores when the variables are re-assessed at a later period; and c) to determine whether the changes, if any, are related to the method of infant feeding. The sociodemographic characteristics aer also evaluated to determine if there are differences among the four infant feeding groups. This may help identify those women who would most likely sustain or switch infant feeding intentions.A survey was done among women confined in a maternity and children's hospital in Manila. The women were selected via simple random sampling and were invited to join if they met set criteria. Two interviews were conducted: during postpartal confinement and at 6 to 8 weeks postpartum. Data were gathered through the use of a pre-tested interview schedule. Data analyses included descriptive statistics, frequency distribution, chi-square, two-way repeated measures design, ETA squared and least significant difference.The final sample consisted of 93 women who were classified into four infant feeding groups: 1) sustained non-berast-feeding; 2) sustained breast-feeding; 3) switched to breast-feeding; and 4) switched to non-breast-feeding.The study found:1. Employment status is associated with sustaining of the infant feeding intention; however, civil status and educational attainment were not associated with sustaining of the infant feeding intention.2. Maternal attitudes was not associated with sustaining the infant feeding intentions to breast-feed or to non-breast-feed.3. Social influences and perceived behavioral control over breast-feeing are associated with sustaining the intention to breast-feed; however, they were not associated with sustaining the intention to non-breast-feed.4. There are significant differences between the means of the variables measured during postpartal confinement and at 6 to 8 weeks postpartum.5. Mild to good associations were found between the variables and the infant feeding group.6. Differences were noted between the means of the particular infant feeding groups of the variables.This study highlights the importance of the assessment of maternal attitudes, social influecnes and perceived behavioral control as these factors and their changes influence the infant feeding intention and method of infant feeding. Based on the findings, the following are the recommendations: 1) use of an assessment tool, such as the interview schedule used, to identify women who prefer non-berast-feeding or are prone to premature weaning from breast-feeding; 2) Occupational Health Nurses Association of the Philippines (OHNAP) should develop and implement policies which focus on the needs of breast-feeding women who work; 3) breast-feeding classes should include topics which show how to prevent and deal with problems related to breast-feeding and should include the participation of social influences; and 4) conduct of a similar study among multiparas and in non-hospital-based settings.